2016
DOI: 10.1002/cncr.30489
|View full text |Cite
|
Sign up to set email alerts
|

An entertainment‐education colorectal cancer screening decision aid for African American patients: A randomized controlled trial

Abstract: BACKGROUND Colorectal cancer screening rates for African American patients remain sub-optimal. Patient decision aids designed with an entertainment-education approach have been shown to improve saliency and foster informed decision making. The purpose of this investigation was to assess whether an entertainment-education decision aid tailored for African American patients improved patients’ decision making, attitudes, intentions, or colorectal cancer screening behavior. METHODS Eighty-nine participants were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 33 publications
2
54
0
Order By: Relevance
“…Slightly more than half (56%; n = 23) of the studies included only participants aged 50 years and older, while five (12%) included participants starting at age 45 years, three (7%) included participants younger than 45. Twelve of the studies (29.27%) reported demographics specific to African-American men [ 50 , 52 , 56 , 57 , 59 , 60 , 63 , 66 , 71 , 74 , 82 , 84 ]. In the studies aimed at increasing CRC screening uptake among African-American men, the intervention components most frequently employed (among 135 interventions types utilized) were telephone encounters or education (18%; n = 25), mailed or electronically sent educational materials (13%; n = 18), FIT or other CRC stool-based screening kits (mailed or administered in person) (13%; n = 17), patient navigation (10%; n = 13), and printed materials given to individuals in person (12%; n = 16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slightly more than half (56%; n = 23) of the studies included only participants aged 50 years and older, while five (12%) included participants starting at age 45 years, three (7%) included participants younger than 45. Twelve of the studies (29.27%) reported demographics specific to African-American men [ 50 , 52 , 56 , 57 , 59 , 60 , 63 , 66 , 71 , 74 , 82 , 84 ]. In the studies aimed at increasing CRC screening uptake among African-American men, the intervention components most frequently employed (among 135 interventions types utilized) were telephone encounters or education (18%; n = 25), mailed or electronically sent educational materials (13%; n = 18), FIT or other CRC stool-based screening kits (mailed or administered in person) (13%; n = 17), patient navigation (10%; n = 13), and printed materials given to individuals in person (12%; n = 16).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-nine studies [ 45 , 46 , 48 , 50 52 , 54 66 , 69 , 71 , 73 75 , 77 , 79 81 , 83 , 84 ] in the RCT category were largely rated as unclear risk, yet 20 of the studies had low risk on random sequence generation (i.e., description of randomization procedure) [ 50 52 , 56 63 , 69 , 74 , 75 , 79 81 ]. The majority of the studies ( n = 13) did not explain or detail if any blinding of the participants and/or personnel in group allocation occurred, which included 18 studies with an unclear risk on allocation concealment [ 48 , 50 , 52 , 54 , 55 , 57 , 63 66 , 71 , 74 , 77 , 79 , 80 , 83 ]. Either listed as a supplement in the manuscript or published elsewhere, only 5 studies [ 50 , 57 , 58 , 61 , 80 ] reported their study protocol.…”
Section: Resultsmentioning
confidence: 99%
“…This review provides support for the use of decision aids among vulnerable sub-populations as a method of educating patients about their options and allowing patients to clarify their preferences regarding test features and screening modalities. 43 , 87 89 …”
Section: Discussionmentioning
confidence: 99%
“… 23 Chart review at three months after the study visit confirmed colorectal cancer screening test orders and completion. 68 …”
Section: Explanation and Elaboration Of Sundae Guidelines Itemsmentioning
confidence: 99%